Firm heterogeneity and the aggregate labour share - Matteo Richiardi; Luis Valenzuela (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2023)
We propose a model-based decomposition method for the aggregate labour share in terms of the first moments of the joint distribution of TFP, market power, wages and prices, and apply it to UK manufacturing using firm-level data for 1998-2014. Contrary to a narrative focussing on increasing disparities between firms, the observed decline in the aggregate labour share over the period is driven entirely by the decline in the labour share of the representative firm, mostly due to an increasing disconnect between average productivity and real wages. Changes in the dispersion of firm-level variables have contributed to slightly contain this decline.
Keywords: 330; Organizations And Firms; Labour Economics; Wages And Earnings; Economics; Labour Market